2018
DOI: 10.1002/sctm.17-0229
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Osteogenic Enhancement of Stem Cells in Human Bone Marrow Using a Glycogen-Synthease-Kinase-3-Beta Inhibitor Improves Osteogenic Efficacy In Vitro and In Vivo

Abstract: Non‐union defects of bone are a major problem in orthopedics, especially for patients with a low healing capacity. Fixation devices and osteoconductive materials are used to provide a stable environment for osteogenesis and an osteogenic component such as autologous human bone marrow (hBM) is then used, but robust bone formation is contingent on the healing capacity of the patients. A safe and rapid procedure for improvement of the osteoanabolic properties of hBM is, therefore, sought after in the field of ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…A previous study demonstrated that BIO can promote the formation of cell mineralized nodules, which is consistent with our results. Moreover, BIO can promote osteogenic differentiation of bone marrow mesenchymal stem cells and dental pulp stem cells by upregulating ALP activity and expression of osteogenic genes. The potential mechanism of stimulation of osteogenesis by BIO may involve the activation of the Wnt signaling pathway in PDLSCs. Wnt family proteins inhibit apoptosis of mature osteoblasts through the classical and nonclassical pathways, thus extending the lifespan of osteoblasts .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that BIO can promote the formation of cell mineralized nodules, which is consistent with our results. Moreover, BIO can promote osteogenic differentiation of bone marrow mesenchymal stem cells and dental pulp stem cells by upregulating ALP activity and expression of osteogenic genes. The potential mechanism of stimulation of osteogenesis by BIO may involve the activation of the Wnt signaling pathway in PDLSCs. Wnt family proteins inhibit apoptosis of mature osteoblasts through the classical and nonclassical pathways, thus extending the lifespan of osteoblasts .…”
Section: Discussionmentioning
confidence: 99%
“…To validate the effect of ionic dissolution products on some of the key signaling pathways, we treated hMSCs with Si, Mg, and Li for 14 days in the presence and absence of cWnt inhibitor (10 M cardamonin; Cayman Chemicals) and MAPK inhibitor (5 M PD185342; Abcam). Both cWnt signaling (39,40) and MAPK/ERK signaling (41) are implicated in osteogenesis and are highlighted in our GO analysis. Western blot was performed on day 14 to evaluate the effect on ALP production (fig.…”
Section: Nanosilicates and Its Dissolution Products Trigger Lineage-s...mentioning
confidence: 96%
“…BIO is a small molecule that targets the glycogen synthase kinase-3 (GSK-3) [ 26 ]. A previous report demonstrated that BIO enhanced alkaline phosphatase (ALP) activity and osteogenesis-related gene expression in osteoprogenitor cells [ 27 ]. Similarly, BIO accelerated the in vitro chondrogenesis of mouse bone marrow mesenchymal stem cells (BMSCs), demonstrated by the upregulation of cartilage-specific gene expression [ 28 ].…”
Section: Introductionmentioning
confidence: 99%